DIGITAL MULTILEVEL SYSTEM OF TRANSPARENCY MANAGEMENT OF FINANCIAL RELATIONS - ZAKHARKIN, Oleksii; NEBABA, Natalia; LEBID, Oksana; ZMIENKO, Vitaly; KORNEYEV, Maxim (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the application of modern digital technologies, platforms, and tools in the system to ensure the transparency of financial relations at various levels of the economic system. The analysis of recent studies has shown that this problem is not sufficiently disclosed in the works of domestic and foreign scientists. The development of digital technologies opens up opportunities for the implementation and use of various platforms and tools that contribute to transparency in the financial sphere at various levels. These tools are the foundation for creating a digital multi-level management system that supports the transparency of financial relations. The principles of operation and information content of the open data platform in the field of public finance E-data, as well as its components - the state web portal of the budget for citizens "Open budget", the single web portal for the use of public funds "Spending", the portal of the register of projects of MFIs, were considered projects. The role of the Prozorro platform, the Dozorro portal, and the search and analytical system .007 in ensuring the transparency of public procurement, which is a necessary condition for the digital transparency of the financial activities of state and communal enterprises, is analyzed. The digital aspects of the transparency of the financial and credit system are considered, highlighting the role of the NBU and banks, and the importance of bank websites as a tool for ensuring transparency, which helps clients to better understand banking services and promotes their social activity. At the level of corporate finance, information services that play a major role in ensuring digital transparency, such as YouControl, Opendatabot, Vkursi Pro, SMIDA, as well as official websites of companies, are considered. These services provide access to open data, market analytics, business intelligence, and investigations, integrate government data into enterprise management systems, and provide comprehensive data analysis of companies and their activities, contributing to the transparency of business operations and risk reduction. Prospects for further research in this direction are outlined.
Keywords: digital technologies; transparency; financial relations; public finance; financial and credit system; corporate finance; personal finance